Pengaruh Intervensi Carta Obesitas Terhadap Kadar Gula Darah Pada Pasien Diabetes Melitus di Puskesmas Pakuniran. - Nur Faizah; Nafolion Nur Rahmat; Widya Addiarto (STIKes Ibnu Sina Ajibarang, 2023)
Diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycemia and disturbances of carbohydrate, fat and protein metabolism due to defects in insulin secretion, insulin action or both. This study aims to analyze the effect of obesity chart intervention on blood sugar levels in diabetes mellitus patients at the Pakuniran Health Center, Probolinggo Regency. The research design used Quasy experimental design two group pretest-posttest with control group design. The population in this study were all diabetes mellitus patients from January to May as many as 278 respondents. The sample of the study is that there are 32 respondents with diabetes mellitus. Data collection using the pre test, post test Assessment of blood sugar levels. Analyst test using Wilcoxon test. The results of the analysis based on the intervention group found that the p-value was 0.000. Indicates that there is an influence between the pre-test and post-test. Based on the control group, the p-value is 0.865. Indicating that there was no effect between the pre-test and post-test, while the differences in blood sugar levels in the pre and post control and intervention groups found that the p-value was 0.007, indicating that there was an effect between the actions in the intervention and control groups.Giving obesity charts to the intervention group has an effect on reducing blood sugar levels in people with diabetes mellitus, because the obesity chart can be understood and applied directly.